Analisis Pelaksanaan Program Usaha Kesehatan Sekolah (UKS) Di SD Kristen Tananahu Kecamatan Teluk Elpaputih - Lea Janwarin; Helda Maahaly Maahaly; Feni The (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2021)
SHU is a government program to improve health services, health education, and foster a healthy school environment or the ability to live a healthy life for school residents. The SHU program is very important to improve the harmonious and optimal growth and development of children so that they become quality human resources. This study aims to describe the implementation of the SHU program at SD Kristen Tananahu, Teluk Elpaputih Subdistrict in 2021. The type of research used in this study was a qualitative research using a qualitative descriptive research design which obtained in-depth data from informants. The total informants in this study were 7 informants. Data collection was carried out through in-depth interviews and observations from Friday - July 2021. The results of the study found that the preparation of the SHU plan at Tananahu Christian Elementary School had been going well, and in accordance with the SHU guidance and development guidelines, the SHU program was carried out in accordance with the three SHU main programs. namely, health education, health services, and fostering a healthy school environment, but there are still shortcomings in facilities and infrastructure and activities that have not been achieved. Keywords: Implementation, program, SHUUKS adalah program pemerintah untuk meningkatkan pelayanan kesehatan, pendidikan kesehatan, dan pembinaan lingkungan sekolah sehat atau kemampuan hidup sehat bagi warga sekolah. Program UKS sangat penting untuk meningkatkan pertumbuhan dan perkembangan anak yang harmonis dan optimal agar menjadi sumber daya manusia yang berkualitas. Penelitian ini bertujuan untuk mengetahui gambaran pelaksanaan program UKS di SD Kristen Tananahu Kecamatan Teluk Elpaputih. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif dengan menggunakan desain penelitian deskriptif kualitatif dimana mendapatkan data yang mendalam dari informan. Total informan dalam penelitian ini yaitu 7 informan. Pengumpulan data dilakukan melalui wawancara mendalam dan observasi dari bulan Juni sampai Juli tahun 2021 . Hasil penelitian didapatkan bahwa penyusunan rencana UKS di SD Kristen Tananahu sudah berjalan dengan baik, serta sesuai dengan pedoman pembinaan dan pengembangan UKS, program UKS dilaksanakan sesuai dengan tiga program pokok UKS yaitu, pendidikan kesehatan, pelayanan kesehatan, dan pembinaan lingkungan sekolah sehat, akan tetapi masih ada kekurangan di sarana dan prasarana serta kegiatan yang masih belum tercapai.Â Kata kunci :Pelaksanaan, Program, UKS